Determination of Plasma Retinol by High Performance Liquid Chromatography, and its Significance in Digestive Diseases - YAMAGUCHI, Hatuhiro; GOTO, Hidemi; TSUKAMOTO, Yoshihisa; SEGAWA, Kose; KURITA, Yasumitsu; NAKAZAWA, Saburo (Japanese Journal of Medicine, 1986)
Plasma retinol was determined by reverse-phase high-performance liquid chromatography in healthy subjects and patients with digestive diseases. The plasma retinol in the healthy control was independent of age (80.5 ± 17.16 μg/dl). On the other hand, the amount of retinol in patient groups was lower than in the healthy control group. It was 30.96 ± 7.16 μg/dl in patients with liver cancer, 38.02 ± 11.63 μg/dl in those with chronic pancreatitis and pancreatic cancer, 45.36 ± 12.63 μg/dl in a patient group with inflammatory bowel disease, 66.25 ± 7.27 μg/dl in the patients of early gastric cancer, and 66.44 ± 10.10 μg/dl in the group with biliary stone. These results and many biological aspects of retinol in human made it clear that, the special attention should be paid to the fluctuation of plasma retinol amount. This was considered to play an important role in causing complications associated with digestive diseases.